Efektivitas Model Pembelajaran Quantum Teaching terhadap Disiplin Belajar dan Hasil Belajar Akidah Akhlak Siswa di Madrasah Tsanawiyah Nahdhotut Tholabah Kecamatan Kampar Kiri Tengah - Abdul Malik (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
This study aims to see the effectiveness of the Quantum Teaching Learning Model on Learning Discipline and Learning Outcomes of Akidah Akhlak Students in Madrasah Tsanawiyah Nahdhotut Tholabah, Kampar Kiri Tengah District. The study used a Quasy Experimental Design. The population of this study were all grade VII students of Madrasah Tsanawiyah Nahdhotut Tholabah. The sample was drawn using purposive sampling technique, namely class VII.A as the experimental class and class VII.B as the control class. The data was collected by means of test and questionnaire techniques. Technical data analysis used the sample t-test. The results of this study indicate that there are differences in learning disciplines between students who take learning with the Quantum Teaching learning model and students who take conventional learning models. The results of the t-test calculation obtained t count 3.043 with a probability (Sig.) 0.004. The probability value (Sig.) 0.004 <0.05 then H0 is rejected. Then there are differences in learning outcomes between students who take learning with the Quantum Teaching learning model and students who take conventional learning. The result of t-test calculation is 5,822 with probability (Sig.) 0,000. The probability value (Sig.) 0.000 <0.05 then H0 is rejected.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//